The landscape, trends, challenges, and opportunities of sustainable mobility and transport - Yong Chen; Chuanjia Li; Wanru Wang; Yuliang Zhang; Xiqun Michael Chen; Ziyou Gao (npj Sustainable Mobility and Transport)
Abstract This paper conducts quantitative analysis and qualitative discussion on 7710 SMT-related publications over the past three decades, presenting the academic landscape of the field, identifying significant research topics and their evolution, and revealing the field’s knowledge diffusion paths. It opens avenues for research like modeling post-pandemic travel behavior and constructing “X-minute” cities, and provides insights into policy formulation, theoretical innovation, and technological reform for policymakers, researchers, and practitioners, respectively.